2017
DOI: 10.1017/jwe.2017.48
|View full text |Cite
|
Sign up to set email alerts
|

Fairtrade Wine Price Dispersion in the United Kingdom

Abstract: This paper analyzes wine price dispersion in the United Kingdom. In particular, we are interested in examining whether Fairtrade wines are different from non-Fairtrade wines. Because Fairtrade wines serve an additional social purpose, one may think that consumers search less aggressively for the outlet with the lowest price, thus allowing for a larger price dispersion than for regular wines. We draw on data for about seven thousand wines from South Africa, Fairtrade and non-Fairtrade, sold in the United Kingdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Today, fair trade ensures that certified wines are produced with safe labor conditions, use environmentally friendly practices and that farmers are paid a base price for their crops (Beirne, 2008). Evidence suggests that the certification has developed real change in the labor market and has allowed for historically disadvantaged farm workers to enter the global wine industry (Moseley, 2008;Niklas et al, 2017).…”
Section: Environmental/eco-certificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, fair trade ensures that certified wines are produced with safe labor conditions, use environmentally friendly practices and that farmers are paid a base price for their crops (Beirne, 2008). Evidence suggests that the certification has developed real change in the labor market and has allowed for historically disadvantaged farm workers to enter the global wine industry (Moseley, 2008;Niklas et al, 2017).…”
Section: Environmental/eco-certificationsmentioning
confidence: 99%
“…While one study found that consumer awareness in North America, for certifications, was low (Schaufele and Hamm, 2017), other studies in Spain (Sellers, 2016) and New Zealand (Forbes et al, 2009) found that consumers are willing to pay a premium for eco-certified wine. For organic wines, there is a propensity to pay a premium price (Remaud et al, 2008;Bazoche et al, 2008) and some consumers would be willing to tolerate higher prices for fair trade certified wine (Niklas et al, 2017). In Italy, researchers found that a sample of consumers had a positive WTP for natural wines (Galati et al, 2019).…”
Section: Literature On Environmental Wine Consumption Willingness To Pay and Consumer Preferencesmentioning
confidence: 99%
“…A possible explanation could be the “warm glow effect” and the resulting higher willingness-to-pay for an ethically superior product. This would contradict Niklas, Storchmann and Vink (2017) who found smaller price dispersions for FT wines in the United Kingdom, indicating a higher degree of search and thus higher price elasticities than for non-FT wines. Likewise, Delmas and collaborators (e.g., Delmas and Grant, 2014; Delmas and Lessem, 2017) could not find any “warm glow” price effect for organic wines in the United States.…”
Section: Resultsmentioning
confidence: 58%
“…Niklas, Storchmann, and Vink (2017) analyze retail prices of FT wines in the United Kingdom. First, they find a significant price discount for FT wines compared to their non-FT counterfactuals—even after controlling for quality, grape variety, age, and producer fixed-effects.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation